2011
DOI: 10.1038/pcan.2010.52
|View full text |Cite
|
Sign up to set email alerts
|

Use of 1,25α dihydroxyvitamin D3 as a cryosensitizing agent in a murine prostate cancer model

Abstract: Cryotherapy has emerged as a primary treatment option for prostate cancer(CaP); however, incomplete ablation in the periphery of the cryogenic lesion can lead to recurrence. Accordingly, we investigated the use of a nontoxic adjunctive agent, Vitamin D3, with cryotherapy to sensitize CaP to low temperature induced, non-ice rupture related cell death. Vitamin D3 (calcitriol) has been identified as a possible adjunct in the treatment of cancer due to its anti-proliferative and anti-tumorigenic properties. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 26 publications
1
32
0
Order By: Relevance
“…Drug resistance, however, could become an issue in vivo [60]. Previous studies from our laboratory have shown the success of adjuvants used for cryosensitization [37,57,[62][63][64][65].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drug resistance, however, could become an issue in vivo [60]. Previous studies from our laboratory have shown the success of adjuvants used for cryosensitization [37,57,[62][63][64][65].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo studies involving prostate cancer have shown the ability of cryosensitizing adjuvants to elevate the minimal lethal temperature for hormone refractory prostate cancer from -40°C to -20°C via pre-treatment with sub-clinical (non-toxic) doses of 5-fl uorocil, taxotere and cisplatin [65,66,71]. Other studies have demonstrated that combinatorial approaches using the active nutraceutical calcitriol (vitamin D 3 ) can result in the elevation of the minimal lethal temperature for prostate cancer to the -10 to -15°C range [57,75,76,78]. Based on these reports coupled with the identifi cation of a delayed molecular cell death response activated following freezing of C2 cells, the use of adjuvant agents, including chemotherapy and immunotherapy agents as well as RTK inhibitors, in combination with CA is an area that may also provide benefi t for treatment of MCT's and as such should be explored in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Through various in vitro , in vivo , and clinical reports, improved cancer destruction at mild sub-freezing temperatures following brief low dose exposure to general or specific apoptotic inducing agents has been shown. In some cases, such as the use of vitamin D 3 as a sensitizing agent, complete prostate cancer cell death has been demonstrated following freezing to temperatures as warm as −10°C in both in vitro and in vivo models [12,61,111]. …”
Section: Adjunctive Therapymentioning
confidence: 99%
“…The diverse techniques have been broadly divided into thermal and non-thermal methods. The mechanisms of cryoablative damage are more completely described when compared to heat-based procedures [11,12,61,111]. …”
Section: Competitive Ablative Therapiesmentioning
confidence: 99%
“…We have previously reported on the ability of calcitriol to synergistically decrease postfreeze prostate cancer cell viability when combined with freezing. 19,20 To this end, investigations were conducted to determine whether this was a result of Figure 3. Asynchronous versus synchronous PC-3 cell response to freezing-alamarBlue metabolic activity data.…”
Section: Impact Of Calcitriol (Vd 3 ) and Freezing On Cell Cyclementioning
confidence: 99%